Influence of chemical degradation and toothbrushing on surface of composites - Torres, Carlos Rocha Gomes [UNESP]; Da Silva, Tânia Mara [UNESP]; Sales, Ana Luísa Leme Simões [UNESP]; Pucci, Cesar Rogerio [UNESP]; Borges, Alessandra Bühler [UNESP] (Jaypee Brothers Medical Publishing, 2015)
Objective: The aim of this study was to evaluate the effect of chemical degradation media associated with brushing on surface roughness (Ra) and Knoop microhardness (KHN) analyses of different composites. Materials and methods: Eighty specimens were prepared for each composite: GrandioSO (Voco), Amaris (Voco), Filtek Supreme (3M ESPE), Filtek LS (3M ESPE). The specimens were divided into four groups according to the immersion in chemical degradation media for 7 days: artificial saliva (control), heptane, 0.02 M citric acid, 70% ethanol. The surface of specimens was submitted to 10950 brushing cycles (200 gm load) in an automatic toothbrushing machine with abrasive slurry. Surface roughness and microhardness measurements were obtained at baseline, after immersion in chemical degradation media and after brushing. Data were submitted to three-way repeated measures ANOVA and Tukey’s test (p < 0.05). Results: The KHN means for composites were: Grandio (153.5± 35.9)a, Filtek Supreme (87.0 ± 24.9)b, Amaris (64.5 ± 24.5)c, LS (69.0 ± 15.3)c; for storage media: artificial saliva (97.3 ± 46.7)a, ethanol (93.3 ± 49.9)a, citric acid (95.8 ± 42.1)a, heptane (87.6 ± 36.7)b; and after treatments: after chemical degradation (104.8 ± 49.7)a, baseline (93.8 ± 42.5)b, after brushing (81.9 ± 36.5)c. The Ra results for composites were: LS (0.15 ± 0.25)a, GrandioSO (0.19 ± 0.24)ab, Filtek Supreme (0.20 ± 0.22)ab, Amaris (0.23 ± 0.37)b; for storage media: artificial saliva (0.18 ± 0.31)a, heptane (0.18 ± 0.25)a, ethanol (0.20 ± 0.26)a, citric acid (0.21 ± 0.28)a, and after treatments: brushing (0.11 ± 0.14)a, after chemical degradation (0.23 ± 0.32)b, baseline (0.24 ± 0.32)b. Conclusion: Brushing after chemical degradation reduced surface roughness values. In general, chemical degradation did not affect composites roughness, but microhardness was significantly reduced. Heptane produced the biggest reduction in composites microhardness. Clinical relevance: The food-simulating solutions and brushing simulating alter the composites properties, and these alterations are material-dependent.
Keywords: Brushing; Chemical degradation; Composites; Knoop microhardness; Surface roughness